Law of the iterated logarithm for estimators of parameters in partially linear errors‐in‐variables models. Issue 3 (17th February 2020) - Wei, Lili
Abstract : Consider the partially linear models Y  =  X T β  +  g ( T ) +  ϵ, where X is measured with additive errors. Under certain conditions, we obtain the law of the iterated logarithm for the estimators proposed by Liang et al of the parameters β and the variance of ϵ .